2018
DOI: 10.5005/jp-journals-10024-2288
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status in Alzheimer\'s Disease Patients: A Descriptive Study in an Italian Population

Abstract: It would be beneficial to introduce trained professional figures in specialized elderly institutions for regular follow-up visits and professional oral hygiene procedures. This task has to be coordinated with the treating physician, family members, and/or caregivers. Knowing that the severity of AD has a negative effect on the oral health status and the type of institutionalization exacerbates it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…We could not extrapolate secular trends in health, because all the measurements for a subject were obtained in a single time. An opposite hypothesis is whether persons with impaired cognition were not prone to maintain the adequate oral hygiene and oral health (D'Alessandro et al, ). Moreover, residual confounders could not be fully excluded in an observational study.…”
Section: Discussionmentioning
confidence: 99%
“…We could not extrapolate secular trends in health, because all the measurements for a subject were obtained in a single time. An opposite hypothesis is whether persons with impaired cognition were not prone to maintain the adequate oral hygiene and oral health (D'Alessandro et al, ). Moreover, residual confounders could not be fully excluded in an observational study.…”
Section: Discussionmentioning
confidence: 99%
“…Alessandro et al . [ 17 ] reported statistically higher values of decayed teeth ( P = 0.005) and tooth loss with less filling in AD patients as compared to controls. A recent large cohort study[ 18 ] conducted over a 10-year period has shown a significant relationship between dementia incidence and number of missing teeth; odds ratios were higher in women than men ( P < 0.001), urban than rural ( P < 0.001), and most higher for age group ≥80 years (odds ratio [OR]: 2.38, confidence interval [CI]: 2.216–2.553, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…reported statistically higher values of periodontal disease measured by chronic periodontal inflammation (CPI) ( P < 0.001) and GI ( P < 0.001) in AD patients as compared to controls. [ 17 ] Gao et al . [ 13 ] have shown 64% of dementia patients with periodontal pockets, 98% had gingival bleeding, however, the difference in periodontal parameters of gingival bleeding, periodontal pocket, and loss of attachment was nonsignificant between dementia and nondementia patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this systematic review and meta-analysis is to highlight the possible association between dental loss and Alzheimer’s disease in order to elaborate on the multifactorial background of this disease and patients’ general health status [24,25].…”
Section: Introductionmentioning
confidence: 99%